Penyebab Terjadinya Kerugian Finansial Pada Perusahaan PT. Arsin Sinjai Kecamatan Sinjai Selatan - Fira Yuniar; Hardiyanti Ridwan; Nurhayani (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2021)
This research departs from a problem regarding the causes of financial loss at PT Arsin Sinjai. This research is included in qualitative research using a phenomenological approach. The subject of this research is the cause of the financial loss of PT. Arsin (Sinjai Water Limited Company). While the object in this study is PT. Arsin (Sinjai Water Limited Company). The data collection techniques are interviews and documents. Meanwhile, the data analysis techniques used were data reduction, data presentation and data verification. The results of this study indicate that several factors that caused financial losses at PT Arsin Sinjai, including: (1) The absence of detailed financial records so that the company did not get accurate information about the amount of costs used and the amount of profits obtained. (2) Do not have business insurance, making it difficult for business owners to save businesses from losses. (3) Monotonous marketing strategy, resulting in a lack of business partners and narrow product introduction. (4) There was fraud by the shop owner in paying the proceeds from the sale of the entrusted product on the grounds that the product that was entrusted was not sold out. (5) There is a damaged product packaging that causes customer satisfaction to be not optimal, which can hinder the product sales process. (6) The absence of application of business risk management is due to business owners who do not realize the importance of implementing business risk management. (7) Costs used in producing products with unbalanced company revenues. (8) There are difficulties for business owners in obtaining additional raw materials used in producing bottled drinking water, in this case the difficulty in obtaining drugs or product preservatives. (9) The quality of the product is poor so that the product is only able to last for three months.